2011
DOI: 10.1002/cpp.683
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning, delusion proneness and stress: an experimental investigation

Abstract: Previous studies have been inconsistent in demonstrating a relationship between delusion proneness and induced stress on reasoning biases. The present study was an experimental investigation of the role of stress in the form of feeling rushed, which has previously been shown to be related to the jumping-to-conclusions reasoning bias for delusion-prone individuals, on the reasoning of delusion-prone individuals. University students (n = 133) completed a measure of delusion proneness and were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…However, it appears likely that the increased JTC was observed because of the increased paranoia. In healthy people, some found that inducing anxiety significantly increases the JTC bias and the levels of state paranoia in high scorers on the CAPE, a psychotic experiences questionnaire (Lincoln et al, 2010a(Lincoln et al, , 2010b) whilst others did not find effect of induced anxiety on the JTC bias (Keefe and Warman, 2011). Given the lack of strong rationale behind an association between JTC and depression or anxiety, we hypothesise that delusions are independently related to JTC and emotions.…”
Section: Introductionmentioning
confidence: 78%
“…However, it appears likely that the increased JTC was observed because of the increased paranoia. In healthy people, some found that inducing anxiety significantly increases the JTC bias and the levels of state paranoia in high scorers on the CAPE, a psychotic experiences questionnaire (Lincoln et al, 2010a(Lincoln et al, , 2010b) whilst others did not find effect of induced anxiety on the JTC bias (Keefe and Warman, 2011). Given the lack of strong rationale behind an association between JTC and depression or anxiety, we hypothesise that delusions are independently related to JTC and emotions.…”
Section: Introductionmentioning
confidence: 78%
“…Several studies even found delusions or delusion proneness only to be associated with reasoning biases when the stimulus material was more emotional (Warman & Martin, 2006), self-referent (Warman et al, 2007) or based on visual or auditory material (Colbert, Peters, & Garety, 2010;Ziegler et al, 2008). In addition, several recent studies in clinical and non-clinical populations have shown that JTC increases under emotional arousal (Ellett, Freeman, & Garety, 2008;Keefe & Warman, 2010;Lincoln, Lange, Burau, Exner, & Moritz, 2010;Moritz et al, in press). Although these findings indicate that the JTC bias might become stronger the more emotionally salient or self-referent a situation is, no study has directly investigated whether it becomes more pronounced when persons have to deal with delusion-relevant situations.…”
Section: Introductionmentioning
confidence: 92%
“…The JTC bias has been well-researched since its initial identification. Research suggests the JTC bias is evident in people with delusions or delusion proneness when material is more emotional (Warman & Martin, 2006), is self-referent (Warman, Lysaker, Martin, Davis, & Haudenschield, 2007), increases under emotional arousal (Keefe & Warman, 2011) and is delusion specific rather than schizophrenia specific (Lincoln, Ziegler, Mehl, & Rief, 2010).…”
Section: Introductionmentioning
confidence: 99%